KONTRIBUSI MOTIVASI DAN MINAT BELAJAR TERHADAP KEMAMPUAN BERBICARA BAHASA INGGRIS MAHASISWA PROGRAM STUDI BIMBINGAN KONSELING STKIP NIAS SELATAN - LAIA, BESTARI (JURNAL EDUCATION AND DEVELOPMENT, 2018)
Thi research is motivated by the background of the lack of enthusiasm in learning, passivity in the learning process, shame in conveying what is in his mind, etc. in addition, students do not achieve the expected competencies in each meeting. Based on the background of the problem, the formulation of the problem is how much is the contribution of motivation and interest in learning to the ability of the english speaking of the Guidance and Counseling Students, STKIP South Nias? The type of the research used is quantitative research with descriptive-correlational research approach. The sample of the study were 79 students. The research instrument is a questionnaire. Hypothesis testing is done using simple and multiple linear regression formulas. Based on the results of data analysis, the results of multiple regression analysis variables X1 and Variable X2 on variable Y shows that Tcount of motivation and interest in learning is 6,343 and 5,884 with a significant level of 0,000 and t table is 1,990, this means that tcount > t table then Ha is accepted, meaning a significant regression coefficient. Thus, it can be concluded that there are significant contributions to motivation and interest in learning in English speaking skill of the Guidance and Counseling Students, STKIP South Nias.